Endoscopic management of tissue‐engineered tracheal graft stenosis in an ovine model. (27th March 2017) - Pepper, Victoria K.; Onwuka, Ekene A.; Best, Cameron A.; King, Nakesha; Heuer, Eric; Johnson, Jed; Breuer, Christopher K.; Grischkan, Jonathan M.; Chiang, Tendy
Abstract : Objective: To evaluate the safety and efficacy of bronchoscopic interventions in the management of tissue‐engineered tracheal graft (TETG) stenosis. Study Design: Animal research study. Methods: TETGs were constructed with seeded autologous bone marrow‐derived mononuclear cells on a bioartificial graft. Eight sheep underwent tracheal resection and orthotopic implantation of this construct. Animals were monitored by bronchoscopy and fluoroscopy at 3 weeks, 6 weeks, 3 months, and 4 months. Bronchoscopic interventions, including dilation and stenting, were performed to manage graft stenosis. Postdilation measurements were obtained endoscopically and fluoroscopically. Results: Seven dilations were performed in six animals. At the point of maximal stenosis, the lumen measured 44.6 ± 8.4 mm 2 predilation and 50.7 ± 14.1 postdilation by bronchoscopy ( P = 0.3517). By fluoroscopic imaging, the airway was 55.9 ± 12.9 mm 2 predilation and 65.9 ± 22.4 mm 2 postdilation ( P = 0.1303). Stents were placed 17 times in six animals. Pre‐ and poststenting lumen sizes were 62.8 ± 38.8 mm 2 and 80.1 ± 54.5 mm 2 by bronchoscopy ( P = 0.6169) and 77.1 ± 38.9 mm 2 and 104 ± 60.7 mm 2 by fluoroscopy ( P = 0.0825). Mortality after intervention was 67% with dilation and 0% with stenting ( P = 0.0004). The average days between bronchoscopy were 8 ± 2 for the dilation group and 26 ± 17 in the stenting group ( P = 0.05). One hundred percent of dilations and 29% of stent placements required urgent follow‐up bronchoscopy ( P = 0.05). Conclusion: Dilation has limited efficacy for managing TETG stenosis, whereas stenting has a more lasting clinical effect. Level of Evidence: NA. Laryngoscope, 127:2219–2224, 2017